Prototype Sistem Monitoring Suhu dan Kelembaban Otomatis pada Greenhouse Berbasis IoT - Nisaul Fitri; Imam Muslem; Riyadhul Fajri (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
Greenhouse is a modern agricultural solution that creates optimal conditions for plant growth, especially amidst climate change and food crises. The purpose of this project is to build an IoT-based system that automatically controls temperature and humidity, using Telegram as the management platform. The system uses the DHT11 sensor for environmental monitoring, NodeMCU ESP8266 for Wi-Fi connectivity, ESP32 as the actuator controller, and a relay module to control a cooling fan. Environmental data is sent in real-time to Telegram, allowing users to monitor and control the greenhouse remotely. Testing results show the system responds automatically to temperature and humidity changes, sends notifications, and activates the cooling fan accurately. Integration with Telegram enhances remote management, energy efficiency, and microclimate stability within the greenhouse